Passenger Satisfaction of Public Bus Services:: A Case Study on Chandra-Hemayetpur Route in Savar - Rahman, Mohammad Mizanur (The Jahangirnagar Review, 2024)
Efficient and reliable bus services are essential components of a sustainable urban transportation system. In densely populated countries like Bangladesh, where mobility challenges are exacerbated by rapid urbanization, understanding the existing bus service conditions and customer satisfaction levels becomes crucial. This study employs a comprehensive approach to assess the current state of bus services and analyze customer perceptions in Chandra-Hemayetpur Route in Savar, Dhaka. Through a combination of quantitative surveys and qualitative interviews, 18 factors were examined including bus availability, comfort in bus, bus fare rate, delay time and accessibility. Moreover, customer satisfaction was also measured trough principal component analysis with the regression model and identify areas for improvement in the bus service. The findings of this research highlight the critical issues within the four component system, such as bus condition, driver’s skills, delay time; comfort in bus; uncomfortable space in bus seat; contractor behavior and crime in the bus. The research found that a significant proportion of bus passengers, above 50%, expressed dissatisfaction or high levels of dissatisfaction with the 18 factors assessed in the Chandra - Hemayetpur route segment of Savar. The total satisfaction level is 3.30, suggesting a proximity to dissatisfaction on the Likert scale (1 to 5; where 4 = dissatisfied). The insights from this study provide valuable guidance for policymakers and transport authorities to enhance the quality of bus services, thereby fostering a more efficient and customer-oriented public transportation network. This research contributes to the broader discourse on satellite town to city connecting road in developing nations and underscores the significance of addressing public transportation challenges for sustainable urban development.